College Dropouts: A View from Two Schools - Brooks, William; Emery, Lawrence (Canadian Journal of Counselling and Psychotherapy, 2012)
A questionnaire was administered to students who withdrew from two academic institutions — a teachers' college and a state university — to study their reasons for leaving. The responses were classified into five categories: academic, health and family, financial, school environment, and other. The most important reason for students' withdrawal appeared to be their feeling that the institution did not offer an academic experience that met their personal objectives.